2019
DOI: 10.1177/0269216319854944
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and prevalence of delirium across palliative care settings: A systematic review

Abstract: Background: Delirium is a common and distressing neurocognitive condition that frequently affects patients in palliative care settings and is often underdiagnosed. Aim: Expanding on a 2013 review, this systematic review examines the incidence and prevalence of delirium across all palliative care settings. Design: This systematic review and meta-analyses were prospectively registered with PROSPERO and included a risk of bias assessment. Data sources: Five electronic databases were examined for primary research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 77 publications
(272 reference statements)
2
91
1
6
Order By: Relevance
“…Unlike the ICD-11, the DSM-5 also makes the distinction between hyperactive, hypoactive and mixed delirium [11]. While hyperactive and mixed subtypes are more precisely and easily identified due to excessive psychomotor activity, hypoactive delirium is often overlooked, although it may be predominant in palliative care with approximately 40% of delirium patients [1].…”
Section: Evaluate Changes In Attention and Awarenessmentioning
confidence: 99%
“…Unlike the ICD-11, the DSM-5 also makes the distinction between hyperactive, hypoactive and mixed delirium [11]. While hyperactive and mixed subtypes are more precisely and easily identified due to excessive psychomotor activity, hypoactive delirium is often overlooked, although it may be predominant in palliative care with approximately 40% of delirium patients [1].…”
Section: Evaluate Changes In Attention and Awarenessmentioning
confidence: 99%
“…An earlier systematic review of the cognitive effects of opioids in cancer reported an association between opioid use and poorer performance on neuropsychological testing, albeit of uncertain clinical signi cance 15 . Delirium is a distressing cognitive disturbance that occurs frequently in the palliative care population; a systematic review reported a delirium point prevalence of 35% on admission to an inpatient palliative care unit and a prevalence ranging up to 88% in the last hours to days before death 46 . One inpatient hospice study reported a prevalence rate of 9.8% for subsyndromal delirium, which may manifest as cognitive impairment without necessarily meeting the full criteria for a delirium diagnosis 47 .…”
Section: Broader Contextmentioning
confidence: 99%
“…[1] Patients in specialist palliative care units (SPCUs) are at increased risk of delirium. [2] Approximately one third of patients have delirium on admission and 58-88% in the weeks or days preceding death. [2] Delirium is distressing for the patient, their family, friends and healthcare staff, [3] and reduces patients' ability to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Approximately one third of patients have delirium on admission and 58-88% in the weeks or days preceding death. [2] Delirium is distressing for the patient, their family, friends and healthcare staff, [3] and reduces patients' ability to communicate. [4] Fluctuating symptoms need regular, systematic assessment of delirium, [5] which is rarely implemented.…”
Section: Introductionmentioning
confidence: 99%